Drift Characteristics of DONET Pressure Sensors Determined From In-Situ and Experimental Measurements - Matsumoto, Hiroyuki; Araki, Eiichiro (Frontiers in Earth Science, 2021)
DONET, the dense ocean-floor network system for earthquakes and tsunamis, began operations in the Nankai Trough, SW Japan, in 2010. The present study focuses on pressure sensors that are being used as tsunami meters to measure changes in hydraulic pressure. Pressure sensors typically show a drift in their readings over their operational lifespan. DONET pressure sensors can act as geodetic sensors measuring vertical crustal deformation change over time if the sensor drift can be accurately corrected. Monitoring crustal deformation before the occurrence of megathrust earthquakes is performed by discriminating between the vertical crustal deformation and the sensor drift of the pressure sensors. Therefore, in this study, we evaluated the sensor drift shown by the DONET pressure sensors since their deployment into the deep-sea, by removing the tidal component and confirming the occurrence of sensor drift. We evaluated the initial behavior of pressure sensors before deep-sea deployment using our own high-accuracy pressure standard. Our experiment involved 20-MPa pressurization for the pressure sensors under an ambient temperature of 2°C for a duration of 1 month. Some sensor drifts in our experiment correspond in rate and direction to those from the in-situ measurements determined to be in the initial stage. Our experiment suggests that the pre-deployment pressurization of pressure sensors can be an effective procedure to determine the sensor drift after sensor deployment into the deep-sea.